How do German primary school teachers prepare students for science standards? Findings from a video study of the Professional Development Program SINUS for Primary Schools - Dalehefte, Inger Marie; Rieck, Karen (Form@re - Open Journal per la formazione in rete, 2014)
The German professional development program SINUS for Primary Schools (2009-2013) aimed to enhance the quality of science and mathematics instruction in primary schools. The implementation was coordinated and evaluated by the Leibniz Institute for Science and Mathematics Education (IPN) in Kiel, Germany. About 870 schools and 5440 teachers participated. In this article we take a closer look at the scientific methods in science instruction and analyse how these are implemented in instruction to address upcoming science standards in secondary school. The results presented refer to the descriptive video data from eight lessons of SINUS teachers and three lessons of teachers from a control group. The findings from the video study show that the scientific methods geared towards the standards in science for secondary school can also be observed in primary school. The results are discussed in terms of cumulative learning and the importance of coordinating educational content between different types of schools. Il programma di sviluppo professionale per le scuole primarie SINUS (2009-2013) ha l’obiettivo di migliorare la qualità dell’insegnamento di scienze e matematica nella scuola primaria. La ricerca qui presentata è stata coordinata e valutata dal Leibniz Institute for Science and Mathematics Education (IPN) di Kiel, in Germania. Hanno partecipato circa 870 scuole e 5440 insegnanti. In questo articolo si pone l’accento sui metodi scientifici utilizzati per l’istruzione primaria e si analizzano le strategie di attuazione in continuità con gli standard d’istruzione delle scienze nella scuola secondaria. I risultati presentati si riferiscono ai dati descrittivi estrapolati dai video di otto lezioni di docenti del SINUS e tre lezioni del gruppo di controllo. I risultati mostrano che i metodi scientifici orientati verso gli standard di scienze per la scuola secondaria si possono osservare anche nella scuola primaria. I risultati sono discussi in termini di apprendimento cumulativo e si soffermano sull’importanza di coordinare i contenuti educativi tra i diversi ordini di scuola.